Reflection of British Policy towards Kurds in Tegehishtina Rasti (Understanding the Truth) Journal/ based on Norman Fairclough Model” - Abdullah, Abdullsalam; Abdulrahman, Hussein (Humanities Journal of University of Zakho, 2021)
Reviewing and evaluating a literary work in each perspective, as a result, an idea and purposes of a text are illustrated and a researcher chooses, based on own aims, a critical approach or a particular analytic method to obtain the ideas and meanings behind the words. Accordingly, based on its principles, a researcher could get own objectives. Thus, Norman Fairclough is one of the analytical models At the beginning, Fairclough considered the text in a linguistic conception then points out the main articles of the text and analyses the way of their relations with general social theories. Fairclough is an analytical model this presents three levels such as Description, Interpretation, and clarification that is why his model is considered to be the linguistic critical model. The study entitled “Reflection of British Policy towards Kurds in Tegehishtina Rasti (Understanding the Truth) Journal/ based on Norman Fairclough Model” is conducted. Researchers tried to find out the data of the research paper based on the art and linguistic styles that Rae presented in Fairclough’s model as description, interpretation, and clarification so as to know the ideological viewpoint, global journalists , and writers of Journal ( Understanding the truth) about British Policy. The main questions of the research are the following: How can we go through the context by the three levels Fairclough’s Model (description, interpretation, and Explanation) from the surface meaning of the text, and what is the supreme text in the Journal (Understanding the truth)? In conclusion, writer and journalist are not only expressing their viewpoints by linguistic elements and non-linguistic ones while writer directly prepares articles based on the British policy , in terms of weakening of the front lines of the war in eastern Turkey along with the impact on the Kurdish minds.